Decision and Game Theory for Security Third International Conference, GameSec 2012, Budapest, Hungary, November 5-6, 2012. Proceedings - Grossklags, Jens.; Walrand, Jean.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the Third International Conference on Decision and Game Theory for Security, GameSec 2012, held in Budapest, Hungary, in November 2012. The 18 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on secret communications, identification of attackers, multi-step attacks, network security, system defense, and applications security.
Secret Communications -- Identification of Attackers -- Multi-step Attacks -- Network Security -- System Defense -- Applications Security. Identification of Attackers -- Multi-step Attacks -- Network Security -- System Defense -- Applications Security.
Keywords: Computer science; Computer Communication Networks; Data protection; Computer software; Information Systems; Mathematics; Computer Science; Information Systems Applications (incl. Internet).; Computer Communication Networks; Systems and Data Security; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Game Theory, Economics, Social and Behav. Sciences